THE EFFECT OF USING MULTIPLE INTELLIGENCE STRATEGY ON STUDENTS™ ACHIEVEMENT IN WRITING NARRATIVE TEXTS - Sitepu, Roy Batman (TRANSFORM: Journal of English Language Teaching and Learning, 2012)
This study was conducted to find out the effect of using multiple intelligence strategy on students™ achievement in writing narrative texts. The population was the students of grade XI SMA SWASTA KATOLIK 2 Kabanjahe. There were 142 students and 60 of them were taken as the sample based on random sampling technique. Thirty students were taken as control group and others as experimental group (taught by using MI strategy). The instrument used to collect the data was a written test. The data were analyzed by using t-test to show the effect of MI Strategy on students™ achievement in writing narrative text. The results of the analysis showed that t-value 2.73 was higher than t-table 1.67 at the level of significance 0.05 and the degree of freedom (df) 58. It means that the alternative hypothesis is accepted. In other words, it is obvious that MI Strategy can cause significant effect on students™ achievement in writing narrative text.   Key Words: Multiple Intelligence, Writing, Narrative Texts